KEADILAN GENDER DI INDONESIA: ANTARA REALITAS PATRIARKI DAN PELUANG PERUBAHAN - Misbahul Munir; Ratnatus Saidah (MIYAH: Jurnal Studi Islam, 2025)
Gender justice in Indonesia continues to face significant challenges from deeply rooted patriarchy in cultural, social, and religious interpretations. These obstacles include biased religious exegesis, disparities in access to education and the economy, and discrimination in political participation. Data indicate that women's participation in the workforce remains significantly lower than that of men, while gender-based violence continues to rise annually. Additionally, women's representation in political decision-making and policy-making remains low despite the implementation of gender quota policies.This study employs a qualitative method with a literature review approach to analyze the realities of patriarchy and opportunities for change in achieving gender justice in Indonesia. The data sources include reports from women's rights organizations, government policies, and academic literature on Islamic feminism and gender policy reform. The findings reveal that patriarchy remains the primary barrier for women in various aspects of life. However, opportunities for change can be found through three main strategies: inclusive reinterpretation of religious texts, gender-based policy reform, and the utilization of digital media for advocacy. These findings affirm that although patriarchy remains strong, transformation toward a more gender-just society can be achieved through a multidimensional approach involving various social and political actors.